2005
DOI: 10.1007/s00018-004-4416-1
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of domain arrangements in proteins and interaction networks

Abstract: Proteins are composed of domains, which are conserved evolutionary units that often also correspond to functional units and can frequently be detected with reasonable reliability using computational methods. Most proteins consist of two or more domains, giving rise to a variety of combinations of domains. Another level of complexity arises because proteins themselves can form complexes with small molecules, nucleic acids and other proteins. The networks of both domain combinations and protein interactions can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 90 publications
2
88
0
1
Order By: Relevance
“…Proteins are therefore modular, and modularity expresses at different hierarchical levels. In multidomain proteins, domains can be either repeated or combined in defined order (100,(166)(167)(168). However, the topology of domain combinations is highly conserved.…”
Section: The Hierarchical Nature Of the Protein Worldmentioning
confidence: 99%
“…Proteins are therefore modular, and modularity expresses at different hierarchical levels. In multidomain proteins, domains can be either repeated or combined in defined order (100,(166)(167)(168). However, the topology of domain combinations is highly conserved.…”
Section: The Hierarchical Nature Of the Protein Worldmentioning
confidence: 99%
“…12-14 Many earlier studies analyzed domain combinations to better understand how domains work together to promote the function of a protein. [15][16][17] They established that domains combine under selection rather than by chance. 18,19 Specifically, some combinations appear more frequently than others, and the distribution of the number of domain neighbors follows a power law.…”
Section: Introductionmentioning
confidence: 99%
“…[79,80] Wuchty [81] studied co-occurrence networks of the ProDom, Pfam, and Prosite domains, with edges between domains that co-occur in at least one protein. He showed that the resulting network does not have random graph characteristics; rather, it is scale-free.…”
Section: Co-occurrence Networkmentioning
confidence: 99%